2005
DOI: 10.1111/j.1399-0004.2005.00472.x
|View full text |Cite
|
Sign up to set email alerts
|

Sitosterolaemia in Switzerland: molecular genetics links the US Amish‐Mennonites to their European roots

Abstract: Sitosterolaemia is a rare autosomal recessive disease characterized by increased intestinal absorption of plant sterols, decreased hepatic excretion into bile and elevated concentrations in plasma phytosterols. Homozygous or compound heterozygous loss of function mutations in either of the ATP-binding cassette (ABC) proteins ABCG5 and ABCG8 explain the increased absorption of plant sterols. Here we report a Swiss index patient with sitosterolaemia, who presented with the classical symptoms of xanthomas, but al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 38 publications
(49 reference statements)
0
8
0
Order By: Relevance
“…The ABCG8 G574R variant present in the Lancaster Amish has been found in contemporary Switzerland. 23 Haplotype analyses have revealed that the initial Amish index cases and the contemporary case identified in Switzerland share a common haplotype, consistent with a common ancestral source for this variant that originated in Switzerland (or before) and was carried to Pennsylvania by ≥1 emigrants in the early 1700s.…”
Section: Discussionmentioning
confidence: 77%
“…The ABCG8 G574R variant present in the Lancaster Amish has been found in contemporary Switzerland. 23 Haplotype analyses have revealed that the initial Amish index cases and the contemporary case identified in Switzerland share a common haplotype, consistent with a common ancestral source for this variant that originated in Switzerland (or before) and was carried to Pennsylvania by ≥1 emigrants in the early 1700s.…”
Section: Discussionmentioning
confidence: 77%
“…The presence of the homozygous mutation Gly574Arg in the ABCG8 gene has been found previously in the Amish-Mennonite patients where a founder effect has been reported [73].…”
Section: Phytosterolemia or Sitosterolemia: Abcg5/g8 Mutationsmentioning
confidence: 85%
“…Solcà et al [73] performed an haplotype analyses using microsatellite markers spanning 4.9 cM on chromosome 2 and showed that a patient with sitosterolemia of SwissGerman origin and the two Amish-Mennonite probands were identical for markers D2S2174, D2S1761, D2S4009, D2S4014, D2S4015, and D2S4016 encompassing the STSL locus. Other studies reported the same observations [42], and mutations in two tandem ABC genes, ABCG5 and ABCG8, encoding sterolin-1 and 2, respectively, are now known to be mutant in sitosterolemia.…”
Section: Phytosterolemia or Sitosterolemia: Abcg5/g8 Mutationsmentioning
confidence: 99%
“…Several mutations have been reported and provide important insights in to the nature of the inheritance. Founder effects for mutations underlie many of the cases, suggesting that this disease has been present for many generations, perhaps more than 4000 years 85 86. Caucasians seem to carry mutations in ABCG8, whereas Chinese, Japanese and Indian (20% of known cases) patients seem to have mutations in ABCG5 5.…”
Section: Genetic Aspects Of Sitosterolaemiamentioning
confidence: 99%